Morphological Variation among Flowers of Bulbophyllum ovalifolium (Blume) Lindl. (Orchidaceae) in Bali - Atmaja, Muhammad Bima; Utami Wibowo, Aninda Retno; Tirta, I Gede (KnE Life Sciences, 2017)
Bulbophyllum ovalifolium (Blume) Lindl., an epiphyte orchid species was collected from several region in Bali and maintained in “Eka Karya” Bali Botanic Garden. The orchid is a common and widespread species in Southeast Asia, thus makes the flower has high variability. Here a study through morphological characters on the flower was done to give more information and understandable of characteristic range. The species was found at altitude range 700 to 2000 m a.s.l., the morphological observation was conducted on 2014 to 2015 particularly in the flowering season. There were three variants of flower based on the differences on size, colour, and the lip. The character on lip surface was found as spot character with three types of surface: coarsely verrucose, scattered verrucose, and glabrous. Keywords: Bali; Bulbophyllum ovalifolium; morphological variation; orchidaceae; orchidi.